Slovenski izseljenski in zamejski tiski - Janežič, Helena (1858)
As many as one-fifth of people of the Slovenian nationality, members of the national minorities in the neighbouring countries and expatriates, is living outside the borders of the Republic of Slovenia. Slovenes living in the border areas of the neighbouring countries are the Slovenian indigenous population. From a historical and cultural point of view, the areas where they live are also Slovenian.A large number of Slovenes began to emigrate to overseas countries in the first half of the 18th century. Most of them emigrated between the mid-19th century and the First World War. The period after the Second World War is characterized by three major emigration waves: the first (1945) refers to political emigrants that lived in Europe during the first years after the war, then they mainly emigrated to overseas countries; in the 1960s, a second wave followed when many workers emigrated to the Western European countries due to more favourable economic conditions; the third wave represents the so-called "brain drain" or experts going abroad. In their new homelands, Slovenes gathered in communities according to religious, political and cultural principles. They cultivated their culture, language, customs and preserved the written word.
Slovenians emigrated from their homeland during different historical periods and they left traces everywhere they had settled. They cultivated their culture, language, customs and the written word. One-fifth of the Slovenian population is living outside the borders of the Republic of Slovenia. A part of rich “production” of the Slovenian diaspora is now available in digitized form on the dLib.si portal, where you can browse through various journals and numerous books.